Three-year outcomes of cystotomy for cystoid macular edema secondary to retinal vein occlusion - Yasuyuki Sotani; Hisanori Imai; Hiroko Yamada; Akiko Miki; Makoto Nakamura (PLoS ONE, 2025)
This retrospective observational study evaluated the three-year clinical outcomes of cystotomy for managing refractory cystoid macular edema (CME) secondary to retinal vein occlusion (RVO). A total of 23 eyes from 23 patients (10 males, 13 females) with CME secondary to RVO (RVO-ME) who underwent cystotomy at Kobe University Hospital between September 2014 and July 2021 were reviewed, with a minimum follow-up of 3 years. Clinical parameters such as age, sex, best-corrected visual acuity (BCVA), central retinal thickness (CRT), number of treatments (anti-vascular endothelial growth factor injections, sub-Tenon triamcinolone acetonide injections, microaneurysm photocoagulation, and pars plana vitrectomy), number of outpatient visits, presence of fibrinogen clot removal, and recurrence were retrospectively analyzed. The mean age was 72.3 ± 10.3 years. Mean BCVA improved from 0.33 ± 0.24 logarithm of the minimum angle of resolution preoperatively to 0.21 ± 0.22 at 3 years (p < 0.001). CRT significantly decreased from 504.7 ± 118.2 μm to 295.2 ± 87.4 μm (p < 0.001). The average annual number of total treatments decreased from 3.7 ± 1.8 to 1.1 ± 3.1 (p < 0.001), and outpatient visits decreased from 11.8 ± 4.0 to 4.4 ± 3.2 (p < 0.001). Fibrinogen clot removal was performed in nine eyes. Recurrence was observed in eight eyes. Cystotomy appeared to be a promising surgical option for managing refractory RVO-ME.